2017
DOI: 10.15406/jabb.2017.02.00031
|View full text |Cite
|
Sign up to set email alerts
|

Production of Glyceryl Monostearate by Immobilized Candida Antarctica B Lipase in Organic Media

Abstract: Chemical methods of synthesizing monoglycerides (MGs) produce mixture of acylglycerols making the synthesis of MGs of a single fatty acid type not possible through this route. Lipases due to their selectivity and specificity offer a useful way of synthesizing highly purified single fatty acid containing monoglycerides. Glyceryl monostearate (GMS), a nonionic amphiphilic monoglyceride of glycerol and stearic acid is widely used as emulsifier in food, cosmetic, pharmaceutical and textile industry. In the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The tocopherol analysis, used 292–298 nm UV spectrometer as the detector, while the wavelength of DAG and MAG occurred at 210 nm (Turkan & Kalay, 2006). In addition, monostearate has a wavelength of 208 nm (Kavadia et al., 2017). Possibly, this could explain interference detected during tocopherol analysis after deodorisation.…”
Section: Resultsmentioning
confidence: 99%
“…The tocopherol analysis, used 292–298 nm UV spectrometer as the detector, while the wavelength of DAG and MAG occurred at 210 nm (Turkan & Kalay, 2006). In addition, monostearate has a wavelength of 208 nm (Kavadia et al., 2017). Possibly, this could explain interference detected during tocopherol analysis after deodorisation.…”
Section: Resultsmentioning
confidence: 99%
“…Odaneth and colleagues previously showed that stearoyl-glycerol synthesis was successfully achieved by performing an esterification using glycerol and stearic acid [25]. Herein, we adapted this strategy that was key for the synthesis of 1-LG-d 5 , the latter being commercially unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…For the synthesis of 1-LG-d 5 , we followed a previously documented strategy involving the enzyme Novozym 435 [25]. In brief, LA and glycerol-d 5 (0.2 and 0.6 mmol, respectively) were dissolved in tert-butanol (1.2 mL).…”
Section: Synthesis and Purification Of 1-lg-dmentioning
confidence: 99%
“…The chemical method of MGS synthesis produce a mixture of acylglycerols (DGS, and tryacylglycerols) and make the synthesis of MG from a single fatty acid type impossible by this route [5]. In addition, because glycerol and fatty acids react spontaneously at 110 °C and the reaction proceeds significantly at higher temperatures, it is difficult to prevent the formation of DGS and triglycerides during direct esterification at higher temperatures [6].…”
Section: Introductionmentioning
confidence: 99%